Osteotomía de Akin con grapa de comprensión - Soriano Medrano, Alfredo; Martínez Boix, Cristina; Villa Fuertes, Alejandro; Pérez del Pozo, Mª Del Carmen (Revista Internacional de Ciencias Podológicas, 2007)
Akin osteotomy requires an stable fixation for a correct resolution. We can use different techniques and instruments for this internal fixation like compression staples, this sataples present numerous advantages in opposed to other internal fixation in podiatric surgery. The intraoperating technique, postsurgical handling and advantages/disadvantages of this technique are described in this paper.